L’encensament i el seu context historicolitúrgic = Incensation and its historical and liturgical context - Llongueras, Lourdes de Sanjosé i (Miscel·lània litúrgica catalana, 2024)
In this article we provide an historical-liturgical approach to the rite of incensation, based on Old Testament and New Testament texts and early Christian writers from Justin to Saint Ephraim of Syria. We analyse the Ordo romanus, incensation at the consecration of high altars and other ceremonies involving this rite.